AGAINST KALĀM FOUNDATIONALISM: IBN TAYMIYYAH’S EPISTEMOLOGY AND ITS STRUCTURAL CONVERGENCE WITH WITTGENSTEINIAN FIDEISM - Munir Munir; M. Rachmatullah Arken; Mohd. Roslan Mohd Nor (Peminat Ilmu Ushuluddin, 2025)
This article examines whether Ibn Taymiyyah’s rejection of taqdīm al-ʿaql, the kalām principle assigning rational argument priority over apparent scriptural meaning, constitutes an independent epistemological theory, and whether that theory shares structural features with Wittgensteinian post-foundationalism as developed by D. Z. Phillips and Norman Malcolm. The analysis applies a two-stage method combining Davidsonian interpretive charity with a Lakatosian distinction between the hard core and protective belt of Ibn Taymiyyah's epistemological program, drawing primarily on the Darʾ Taʿāruḍ al-ʿAql wa-al-Naql, al-Radd ʿalā al-Manṭiqiyyīn, and Bayān Talbīs al-Jahmiyya. The study identifies four structural homologies between Ibn Taymiyyah's epistemology and Phillips-Malcolm fideism, alongside three irreducible ontological divergences at the level of correspondence theory, cosmological realism, and the transcultural scope of fiṭra. These findings weaken the irrationalism charge associated with Laoust, Massignon, and Wolfson, demonstrating that Ibn Taymiyyah's resistance to kalām operates as a coherent epistemological position rather than fideistic evasion.